2003
DOI: 10.1029/2002gl016855
|View full text |Cite
|
Sign up to set email alerts
|

Mountaintop and radar measurements of anthropogenic aerosol effects on snow growth and snowfall rate

Abstract: [1] A field campaign designed to investigate the second indirect aerosol effect (reduction of precipitation by anthropogenic aerosols which produce more numerous and smaller cloud droplets) was conducted during winter in the northern Rocky Mountains of Colorado. Combining remote sensing and in-situ mountain-top measurements it was possible to show higher concentrations of anthropogenic aerosols ($1 mg m À3) altered the microphysics of the lower orographic feeder cloud to the extent that the snow particle rime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
167
4
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(188 citation statements)
references
References 10 publications
13
167
4
4
Order By: Relevance
“…Ice crystals did form in the clouds after maturing at temperatures of −12°C or colder, which were capable of producing graupel when falling into younger parts of the clouds that still contained large amounts of supercooled water. This indicates that IN did exist in this polluted air, but the rate of growth of the ice hydrometeors is rather slow in clouds with very small cloud drops, as already shown in previous studies elsewhere (Borys et al, 2003).…”
Section: The Effects Of Aerosols On Ice Precipitationsupporting
confidence: 54%
See 2 more Smart Citations
“…Ice crystals did form in the clouds after maturing at temperatures of −12°C or colder, which were capable of producing graupel when falling into younger parts of the clouds that still contained large amounts of supercooled water. This indicates that IN did exist in this polluted air, but the rate of growth of the ice hydrometeors is rather slow in clouds with very small cloud drops, as already shown in previous studies elsewhere (Borys et al, 2003).…”
Section: The Effects Of Aerosols On Ice Precipitationsupporting
confidence: 54%
“…This slows the drop coalescence and in turn the conversion of cloud water into rain drops (Rosenfeld, 2000;Hudson and Yum, 2001;McFarquhar and Heymsfield, 2001;Yum and Hudson, 2002;Borys et al, 2003;Andreae et al, 2004;Hudson and Mishra, 2007;Rosenfeld et al, 2008;Flossmann and Wobrock, 2010). It also slows the mixed phase precipitation forming processes by decreasing the riming and growth rate of ice hydrometeors (Borys et al, 2003;Saleeby et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mixed-phase orographic clouds, where ice crystals co-exist with water droplets, a decrease in the size of Published by Copernicus Publications on behalf of the European Geosciences Union. 4304 D. S. Ward and W. R. Cotton: Cold and transition season supercooled cloud droplets reduces the riming efficiency which may lead to a decrease in the liquid water content of precipitation falling as snow or a change in the spatial distribution of the precipitation (Borys et al, 2003;Saleeby et al, 2009). Investigations of precipitation climatology in mountainous regions in the western US have demonstrated a longterm decrease in accumulated precipitation downwind and upslope of urban areas (Givati and Rosenfeld, 2004;Rosenfeld and Givati, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Jirak and Cotton (2006) found similar results along the Colorado Front Range, attributing the lower precipitation to increases in pollution from the urban corridor. Case studies of mixed-phase orographic clouds have also shown a connection between lower precipitation production and local anthropogenic aerosol sources (Borys et al, 2000(Borys et al, , 2003, and recent modeling studies of these clouds by Lynn et al (2007) and Saleeby et al (2009) have demonstrated sensitivity in the precipitation fields to changes in CCN number concentration (N ccn ).…”
Section: Introductionmentioning
confidence: 99%